2021
DOI: 10.3390/ijms22179220
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Introduction of Solid Fat with a High Content of Unsaturated Fatty Acids to Gluten-Free Muffins as a Basis for Designing Food with Higher Health Value

Abstract: Background: Shortenings are high in undesirable nutritionally saturated fatty acids. The aim of the study was to produce gluten-free muffins (GFM) of increased health quality and available to people intolerant to gluten, in which the shortenings were replaced with solid oleogels, consisting of 95% rapeseed oil. Methods: The dough and baked products were subjected to physical, textural, and structural analyses. Moreover, the fatty acids composition, chemical quality of fats extracted from muffins, and color of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Thus, it can be concluded that consumers would find no meaningful difference in the surface color of cookies with shortenings or wax oleogels (ΔE < 6 for all oleogel samples; Table 1). Kupiec et al 24 found that muffins made with wax oleogels (candelilla, sunflower, beeswax) obtained a similar color to the product with shortening, supporting our result. In future, we will further verify this conclusion by sensory analysis.…”
Section: Spread Ratio and Color Of Cookiessupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, it can be concluded that consumers would find no meaningful difference in the surface color of cookies with shortenings or wax oleogels (ΔE < 6 for all oleogel samples; Table 1). Kupiec et al 24 found that muffins made with wax oleogels (candelilla, sunflower, beeswax) obtained a similar color to the product with shortening, supporting our result. In future, we will further verify this conclusion by sensory analysis.…”
Section: Spread Ratio and Color Of Cookiessupporting
confidence: 90%
“…The cookie that contained traditional shortening was used as a control sample. This parameter was calculated based on the following formula: 24 normalΔEgoodbreak=()0.25emL*pL*c2+()0.25ema*pa*c2+()b*pb*c21/2 where L*p, a*p and b*p are the color coordinates of cookies with oleogel, and L*c, a*c and b*c are the color coordinates of the control sample.…”
Section: Methodsmentioning
confidence: 99%
“…The analyzed lipid was characterized by a relatively high values of the atherosclerotic index-above 1 (Table 1), which is typical for shortenings and proves that they are products with low nutritional value [10].…”
Section: Characteristic Of Raw Lipidsmentioning
confidence: 80%
“…Cardiovascular diseases can be countered by a drastic reduction in the consumption of foods rich in saturated fats acids [8,9]. For this reason, much attention is focused on improvement of nutritional profiles of these products by development of low-fat products using fat replacers [10]. Moreover, substitution of fats rich in SFA or TFA in food may contribute to the prevention of overweight and development of obesity [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that oleogels can improve the oxidation resistance of oil [ 98 ] and the lipid fraction in the product [ 99 ]. Publications show the successful replacement of solid fats in bakery products, spreads, sausages, ice cream, and chocolates ( Table 2 ) [ 70 , 81 , 100 ].…”
Section: Trends In Fat Modification Technologymentioning
confidence: 99%